Regional variation in appropriate care for ST-elevation myocardial infarction in Finland. (30th September 2020) - Reissell, E; Lumme, S; Satokangas, M; Manderbacka, K
Abstract: Background: Timely primary percutaneous coronary intervention (PCI) is currently the treatment of choice for ST-elevation myocardial infarction (STEMI). Although cardiac units were established in all central hospitals in late 1990s for sparsely populated Finland, studies have shown that regional variation has increased. Additionally, the dense Finnish hospital network includes non-cardiac facilities where patients may be inappropriately admitted and then transferred for PCI. We aim to investigate the current regional differences in receiving timely PCI, determinants of these variations and the effect of hospital transfers. Methods: Finnish Hospital Discharge Register data on PCIs for STEMI patients in 2015-17 were linked to register data on socio-demographics. In these preliminary analyses we used logistic regression modelling. Results: Our results suggest that there were significant regional differences both for timely PCI in STEMI patients and in the probability of hospital transfers during an episode of care. The regional odds ratios (OR) for receiving PCI on time varied from 0.41 (95% confidence interval 0.33-0.52) to 2.73 (2.09-3.57) compared with the capital region when controlling for age, gender and hospital transfers. The ORs for being transferred during an episode of care varied from 0.26 (0.15-0.44) to 16.6 (11.6-23.6). Patients not transferred were more likely to receive PCI (OR 1.89 (1.67-2.15)). Men received PCI on time more often (OR 1.31 (1.18-1.46)) and women were more likely to be transferred (OR 1.29 (1.15-1.45)). Conclusions: The probability for receiving PCI on time was related to the size of the hospital's population base and academic affiliation and inversely to transfers between hospitals. Hospital transfers during care episode and atypical symptoms often seen in women may cause critical delays for PCI. Other determinants for variation of timely PCI and its effects on equity will be analysed using multilevel modelling. Key messages: Appropriate care for STEMI varies across regions and reflects inept practices in provider network. These findings are more pronounced in women showing persisting gender-related inequity.